MARTIN LISTER’S 1678 AMMONIS CORNU AND THE MISREADING OF HILDOCERAS BIFRONS (BRUGUIÈRE, 1789). AN HISTORICAL INSIGHT ON THE RELEVANCE OF ARTWORK AND DETAILS IN TAXONOMY (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2023)
Hildoceras bifrons (Bruguière, 1789) is a cosmopolite ammonite species from the Lower Jurassic of the Boreal and Mediterranean (Tethys) palaeogeographical provinces. Inter-demic and phylogenetic variability are noticeable, also affecting the most distinctive morphological trait: the spiral groove along the whorl flank. Since the XIX century, however, a number of morphotypes assigned to Hildoceras bifrons (many of which from the Apennines and other Italian localities) lacked a neat spiral groove, replaced by a shallow, variably evident and discontinuous inflection. Buckman (1918) provided a photographic illustration of a specimen he interpreted as corresponding to the holotype, until then represented by a drawing described by Lister (1678) as Ammonis cornu. Buckman’s illustration assessed the well-carved spiral groove as a distinctive feature of the holotype and a trademark of the species. Nevertheless, several authors insisted on referring faintly grooved specimens to Hildoceras bifrons, an attitude thus envisaged as due to their negligence or inaccuracy. In contrast with this view, it is herein argued that, on one hand, the specimen illustrated by Buckman, in quality of holotype or neotype, differs from Lister’s drawing to a point that it may not be the same specimen; on the other hand, Lister’s drawing (never formally invalidated as holotype) could have been legitimately considered representative also of those faintly grooved Hildoceras now assigned to Hildoceras lusitanicum Meister, 1913. This alternative view clarifies the taxonomic approach held by many authors, proving the coherency of their taxonomic work rather than their attitude at a superficial evaluation of diagnostic traits.
Keywords: History of Palaeontology; ammonites; scientific illustrations; Toarcian; Rosso Ammonitico.